Use of Community Treatment Orders in Inpatient Rehabilitation Services in Leicester, Leicestershire and Rutland: Findings From the Leicestershire Inpatient Rehabilitation Outcomes (LIRO) Research - Edvin Sajquim; Kelly Fenton; Katherine Kidd; Sandeep Singh (BJPsych Open, 2025)
Aims: 1. To evaluate and understand the sociodemographic characteristics of the patients admitted to rehabilitation wards who were subjected to CTO. 2. To evaluate the rehabilitation of inpatients discharged with or without CTO in place and compare their readmission rate.